2021
DOI: 10.1111/1462-2920.15659
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of a high‐affinity iron transporter (PiFTR) from the endophytic fungus Piriformospora indica and its role in plant growth and development

Abstract: Summary Iron (Fe) is a micronutrient required for plant growth and development; however, most Fe forms in soil are not readily available to plants, resulting in low Fe contents in plants and, thereby, causing Fe deficiency in humans. Biofortification through plant‐fungal co‐cultivation might be a sustainable approach to increase crop Fe contents. Therefore, we aimed to examine the role of a Piriformospora indica Fe transporter on rice Fe uptake under low Fe conditions. A high‐affinity Fe transporter (PiFTR) fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 55 publications
0
22
0
Order By: Relevance
“…The observation that S. indica ‐inoculated plants could take up three times more P than control plants, over a short period of time (6 h), suggested P transfer capacities in the fungus (Shahollari et al ., 2005), which were later confirmed using P isotope‐tracing in compartmentalized systems (Bakshi et al ., 2015). Further isotope‐tracing studies showed that S. indica is also capable of transferring P and sulphur (S) to maize (Kumar et al ., 2011; Narayan et al ., 2021), and Fe to rice (Verma et al ., 2021). Although the molecular bases for these nutrient transfers on the fungal side are not yet clear, the involvement of the fungal sulphate transporter SiSulT (Narayan et al ., 2021), the iron transporter PiFTR (Verma et al ., 2021) and the phosphate transporter PiPT (Kumar et al ., 2011) is strongly suspected.…”
Section: Mycorrhizal Symbioses In Am Nonhost Lineagesmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation that S. indica ‐inoculated plants could take up three times more P than control plants, over a short period of time (6 h), suggested P transfer capacities in the fungus (Shahollari et al ., 2005), which were later confirmed using P isotope‐tracing in compartmentalized systems (Bakshi et al ., 2015). Further isotope‐tracing studies showed that S. indica is also capable of transferring P and sulphur (S) to maize (Kumar et al ., 2011; Narayan et al ., 2021), and Fe to rice (Verma et al ., 2021). Although the molecular bases for these nutrient transfers on the fungal side are not yet clear, the involvement of the fungal sulphate transporter SiSulT (Narayan et al ., 2021), the iron transporter PiFTR (Verma et al ., 2021) and the phosphate transporter PiPT (Kumar et al ., 2011) is strongly suspected.…”
Section: Mycorrhizal Symbioses In Am Nonhost Lineagesmentioning
confidence: 99%
“…Further isotope‐tracing studies showed that S. indica is also capable of transferring P and sulphur (S) to maize (Kumar et al ., 2011; Narayan et al ., 2021), and Fe to rice (Verma et al ., 2021). Although the molecular bases for these nutrient transfers on the fungal side are not yet clear, the involvement of the fungal sulphate transporter SiSulT (Narayan et al ., 2021), the iron transporter PiFTR (Verma et al ., 2021) and the phosphate transporter PiPT (Kumar et al ., 2011) is strongly suspected. Reciprocal C transfer from the plant to the fungus has not been proven, but it is known that the fungus alters C metabolism in A. thaliana , which could mediate the uptake of monosaccharides from the plant by the fungus (Opitz et al ., 2021).…”
Section: Mycorrhizal Symbioses In Am Nonhost Lineagesmentioning
confidence: 99%
“…It has demonstrated beneficial effects on plant growth under both biotic and abiotic conditions such as drought and saline conditions (Waller et al, 2005;Ghaffari et al, 2016;Jogawat et al, 2016;Abdelaziz et al, 2017;Li et al, 2017;Zhang et al, 2018;Ghorbani et al, 2019). However, although recently progress is being made in the knowledge of the nutrition of certain micronutrients such as magnesium, iron and sulfur (Prasad et al, 2019;Narayan et al, 2021;Verma et al, 2021), there is not much information available on the contribution of this endophyte to the plant nutrition of the main macronutrients, as previous studies to determine its role in plant P nutrition have obtained contradictory results. Although there are data indicating that S. indica does not play any role in the supply of Pi in the symbiosis with barley (Achatz et al, 2010), it has been found that S. indica enhances plant growth by transferring phosphate to host maize plants (Yadav et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Because ethylene is used by plants to inhibit their growth under natural conditions, P. indica changes the ethylene pathway, which in turn may help promote host growth ( Schäfer et al, 2009 ). A recent study indicated that Fe transporter ( PiFTR) ( Verma et al, 2021 ) and sulfate transporter ( SiSulT ) from P. indica ( Narayan et al, 2021 ) play key roles in plant growth and development.…”
Section: Discussionmentioning
confidence: 99%